2021
DOI: 10.3389/fmicb.2021.734854
|View full text |Cite
|
Sign up to set email alerts
|

Fnr Negatively Regulates Prodigiosin Synthesis in Serratia sp. ATCC 39006 During Aerobic Fermentation

Abstract: The well-known Crp/Fnr family regulator Fnr has long been recognized as an oxygen sensor to regulate multiple biological processes, including the switch between aerobic/anaerobic metabolism, nitrogen fixation, bioluminescence, infection, and virulence. In most cases, Fnr was found to be active under anaerobic conditions. However, its role in aerobic antibiotic metabolism has not yet been revealed. In this research, we report that in the model organism, Serratia sp. ATCC 39006, Fnr (Ser39006_013370) negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Prodigiosin was a kind of bacterial secondary metabolites produced mainly by many S. marcescens strains. Various regulating genes involved in prodigiosin biosynthesis have been found in the past two decades, but new regulators, such as RcsB ( Pan et al, 2021 ), CpxA/R ( Qiu et al, 2021 ) and Fnr ( Sun et al, 2021 ), have still been reported continuously. Research of the these genes may help to uncover the regulatory mechanism behind prodigiosin biosynthesis in S. marcescens .…”
Section: Discussionmentioning
confidence: 99%
“…Prodigiosin was a kind of bacterial secondary metabolites produced mainly by many S. marcescens strains. Various regulating genes involved in prodigiosin biosynthesis have been found in the past two decades, but new regulators, such as RcsB ( Pan et al, 2021 ), CpxA/R ( Qiu et al, 2021 ) and Fnr ( Sun et al, 2021 ), have still been reported continuously. Research of the these genes may help to uncover the regulatory mechanism behind prodigiosin biosynthesis in S. marcescens .…”
Section: Discussionmentioning
confidence: 99%
“…ATCC 39006 under aerobic conditions. There is a Fnr binding site between the −10 and − 35 regions of pigA , which inhibits the synthesis of PG by disrupting the binding of the promoter and RNA polymerase ( Sun et al, 2021 ).…”
Section: Synthesis Of Prodigiosinmentioning
confidence: 99%
“…For the former, Fnr negatively regulates carbapenem biosynthesis through CarR, a gene that can encode a pathway specific activator of bacteriostatic carbapenems; For the latter, Fnr can enhance the expression of flagellar genes, which is conducive to bacterial motility. Therefore, it can be seen that knocking out or modifying a gene has both advantages and disadvantages for the bacteria, and the appropriate method should be selected according to the actual situation ( Sun et al, 2021 ). In one study, researchers introduced clusters of biosynthetic genes encoding PGs into Pseudomonas putida and used genome editing tools to make auxiliary proteins required for polyketide synthases (PKSs) and NRPSs more available, leading to increased PG production ( Cook et al, 2021 ).…”
Section: Synthesis Of Prodigiosinmentioning
confidence: 99%
“…Typical pigment-producing microorganisms include Phaffia rhodozyma (yeast, producing red pigments—carotenoids), Monascus sp (fungus, producing monascus red pigments), Blakeslea trispora (fungus, producing orange pigments like beta-carotene), Streptomyces cyaneus (fungus, producing black pigment—melanin), and Serratia sp (bacteria, producing red pigment—prodigiosin) (Chao et al 2018 ; El-Batal et al 2017 ; Kim and Ku 2018 ; Mussagy et al 2021 ; Sun et al 2021 ). Traditional random mutagenesis using ultraviolet (UV), 1-methyl-3-nitro-1-nitrosoguanidine (NTG) and ethyl methane sulfonate (EMS) have greatly improved microbial pigment production (Yolmeh and Khomeiri 2016 ; Yolmeh et al 2017 ).…”
Section: Biosynthesis Of Pigments From Natural Producersmentioning
confidence: 99%